Properties of Stone Mastic Asphalt Slabs Compacted Using a Newly Developed Roller Compactor - Mohd Jakarni, Fauzan (2006)
Pavement mix design procedures and specifications are usually derived from laboratory experiments conducted on materials that are to be used in the field. Therefore, laboratory experiments should be able to simulate to a high degree the conditions in the field, especially in term of compaction procedures. Stone Mastic Asphalt (SMA) is one type of asphalt mixtures that is highly dependent on the method of compaction as compared to conventional Hot Mix Asphalt (HMA) mixtures. As the future trends in asphalt pavement industry all over the world is gradually changing over to SMA due to its excellent performance characteristics, a suitable laboratory compaction method that can closely simulate field compaction is evidently needed. Therefore, this study is conducted in order to evaluate the Stone Mastic Asphalt (SMA) properties compacted using the newly developed Turamesin and thus to determine the ability and performance of Turamesin as an improved laboratory compaction method. This study comprises of three stages. In Study 1, a literature review was conducted in order to establish suitable methods for slab compaction procedures. Preliminary compactions were then performed and data were analyzed to develop correlation between different compactive efforts and properties of the compacted slabs. From the analysis, 8 kgf/cm2 of applied pressure and 75 numbers of passes of the roller compactor were required to achieve the ideal void content of 4%. Also, Turamesin was found to be capable of compacting slab within duration of 15 minutes, enabling 16 cylindrical core specimens of 100 mm to be cored out. In Study 2, a total of 15 slabs from three different types of asphalt binders, namely Grade 60/70, Grade PG76 and Grade 80/100 were prepared, measured and analyzed for consistency in terms of length, width and thickness. The results have indicated that the variability of the measured parameters of length, width and thickness were generally low as indicated by 0.26%, 0.18% and 1.44% of coefficient of variation respectively. Thus, it can be concluded that the slabs were uniformly compacted in terms of physical dimensions, resulted in average area of 590 mm by 500 mm and thickness ranging from 60 mm to 68 mm. Prior to Study 3, 100 mm and 200 mm diameter cylindrical core specimens were cored out from previously prepared SMA slabs, before being subjected to bulk density, air voids and other performance tests. Based on the analysis, it was found that the SMA slabs have uniformly distributed properties throughout the slabs with low percentage of coefficient of variation. The measured properties tend to agree with the expected performance and comparable to the common SMA mixtures performance. Therefore, it can be concluded that Turamesin was capable in compacting SMA slabs with uniformly distributed properties throughout the slab which indicate the efficiency and outstanding performance of Turamesin.